A missional study of Ghanaian Pentecostal churches’ leadership and leadership formation - Peter White (HTS Teologiese Studies/Theological Studies, 2015)
Church leadership plays an important and irreplaceable role in the planting and the configuration of the missional congregation. The key to the formation of missional communities is their leadership. In that regard, this article explores Classical Ghanaian Pentecostal Churches’ leadership and leadership formation from a missiological perspective. This was done through an exposition on their leadership system (structure). It was argued that Classical Ghanaian Pentecostal Churches’ leadership is based on the Fivefold Ministry (Apostle, Prophet, Evangelist, Pastor and Teacher). These leadership functions were therefore discussed in the light of their missiological implication. The conclusion arrived at is that it is not enough to discover one’s spiritual gift or calling; these gifts should be developed and nurtured through mentoring and proper theological education, with the ultimate purpose being to participate in the Missio Dei.